Case Report: Complete Maternal Uniparental Isodisomy of Chromosome 5 (iUPD(5)mat) With PCSK1 Nonsense Variant in an Infant With Recurrent Diarrhea - Qian, Yanyan; Wu, Bingbing; Liu, Renchao; Lu, Yulan; Zhang, Ping; Shao, Caihong; Huang, Ying; Wang, Huijun (Frontiers in Genetics, 2021)
Congenital diarrhea diseases are a heterogeneous group of conditions and are the major cause of neonatal mortality worldwide. Proprotein convertase 1/3 (PC1/3) deficiency has been associated with severe malabsorptive diarrhea, obesity, and certain endocrine abnormalities. We report an infant born to non-consanguineous parents who is diagnosed with PC1/3 deficiency due to nonsense homozygous variant (c.238 C>T, p.Arg80Ter) in the PCSK1 gene, identified by Trio-exome sequencing (Trio-ES). The baby girl presented with recurrent diarrhea, transient liver dysfunction and hypoglycemia. Trio-ES showed complete maternal uniparental isodisomy (iUPD) of chromosome 5. Our finding provides accurate genetic counseling to this family and expands the clinical spectrum of iUPD with pathogenic variants causing recessive disease.